2002
DOI: 10.1002/polb.10298
|View full text |Cite
|
Sign up to set email alerts
|

Multiple melting behavior of poly(butylene succinate). I. Thermal analysis of melt‐crystallized samples

Abstract: The multiple melting behavior of poly(butylene succinate) (PBSu) was studied with differential scanning calorimetry (DSC). Three different PBSu resins, with molecular weights of 1.1 ϫ 10 5 , 1.8 ϫ 10 5 , and 2.5 ϫ 10 5 , were cooled from the melt (150°C ) at various cooling rates (CRs) ranging from 0.2 to 50 K min Ϫ1 . The peak crystallization temperature (T c ) of the DSC curve in the cooling process decreased almost linearly with the logarithm of the CR. DSC melting curves for the melt-crystallized samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 26 publications
7
106
0
1
Order By: Relevance
“…6, the DSC heating thermogram of neat PBS showed two endothermic peaks due to the melting and re-crystallization mechanism (Yasuniwa and Satou 2002). The first melting peak was ascribed to the melting of less perfect crystals.…”
Section: Fig 7 Dsc Cooling Thermograms Of Neat Pbs and Its Biocompomentioning
confidence: 91%
“…6, the DSC heating thermogram of neat PBS showed two endothermic peaks due to the melting and re-crystallization mechanism (Yasuniwa and Satou 2002). The first melting peak was ascribed to the melting of less perfect crystals.…”
Section: Fig 7 Dsc Cooling Thermograms Of Neat Pbs and Its Biocompomentioning
confidence: 91%
“…But for PBSTMA the appearance of the Peak L was seen only when the cooling rate was lower than 58C/min. Yasuniwa and Satou 33 and Qiu et al 34 also found that PBS showed double melting peaks after crystallizing nonisothermally from the melt at a constant cooling rate, which was ascribed to the re-crystallization and melting mechanism. That was to say, the low-temperature and high-temperature peaks in the Figure 8 were attributed to the melting of some amount of the primary crystallites and the melting of the more stable crystals formed through the melt-recrystallization process during the heating scan, respectively.…”
Section: Crystallization Rate Coefficientmentioning
confidence: 93%
“…The reason is due to the melting%recrystal-lization%remelting behavior [11,12,15,17] of PBSu-rich copolymers during the heating process. In the case of PBMPSu 50/50, the T m value was 50.2°C, when the specimen was maintained at RT for more than three days.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The crystalline structure [5][6][7][8][9], and crystallization and melting behavior [10][11][12][13][14][15][16][17][18] of PBSu have been investigated extensively. PBSu has a relatively low biodegradation rate because of its high crystallization rate and high crystallinity.…”
Section: Introductionmentioning
confidence: 99%